Modern equipment for ecology protection (Международный научный журнал «Инженер», 2026)
This article analyzes the significance of modern equipment in ensuring environmental sustainability andprotection. Technologies such as air purification, waste recycling, water resource conservation, and theutilization of renewable energy sources are extensively discussed as means to mitigate environmentalissues. The article also provides information on the state policy being implemented in Uzbekistanregarding environmental protection, the declaration of 2025 as the "Year of Environmental Protectionand Green Economy," and advanced innovations in this field. This study aims to reveal the potential foreffective use of modern technologies in achieving environmental sustainability.